GEOLOGI DAN STUDI PENGARUH LITOLOGI TERHADAP KUALITAS AIRTANAH BERDASARKAN PARAMETER FISIKA, DAN KIMIA DAERAH NGEBEL, PONOROGO, JAWA TIMUR: GEOLOGI DAN STUDI PENGARUH LITOLOGI TERHADAP KUALITAS AIRTANAH BERDASARKAN PARAMETER FISIKA, DAN KIMIA DAERAH NGEBEL, PONOROGO, JAWA TIMUR - Agus Harjanto (Jurnal Ilmiah Geologi PANGEA, 2026)
Administratively, the study area is located in Ngebel District, Ponorogo Regency, East Java Province, covering an area of 25 km² (5 × 5 km). The Ngebel area and its surroundings are characterized by the occurrence of several springs, including both cold and hot springs. The presence of these springs is widely utilized by the local community for daily needs. This study aims to assess spring water quality as a baseline alternative for water quality monitoring in the study area. The methods used to analyze water quality parameters are based on physical and chemical aspects, including Stiff Diagram and Piper Trilinear Diagram analyses. The data were processed using RockWorks 16.0 software to determine water quality types. Based on the Stiff Diagram and Piper Trilinear Diagram, spring water in the study area is dominated by calcium (Ca) as the major cation and bicarbonate (HCO₃⁻ + CO₃²⁻) as the dominant anion, indicating a calcium–bicarbonate water type. The high concentrations of Ca cations and HCO₃⁻ + CO₃²⁻ anions are influenced by the pyroclastic rocks composing the study area. According to the Indonesian Ministry of Health Regulation No. 492/MENKES/PER/IV/2010 concerning water quality standards, spring water quality in the study area varies. A small proportion of samples still meets the quality standards, whereas most samples—particularly hot springs—do not meet clean water quality standards due to acidic pH values, high electrical conductivity and total dissolved solids, as well as elevated concentrations of certain dissolved ions exceeding the permissible limits..Keywords: Ngebel, Springs, Water Quality, Lithological Control